2013
DOI: 10.3892/etm.2013.1223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an aqueous extract of Eucommia on articular cartilage in a rat model of osteoarthritis of the knee

Abstract: Osteoarthritis is a common chronic and progressively degenerative joint condition. The stem bark of Eucommia ulmoides Oliver (a member of the Eucommiaceae family), which is also known as Du-Zhong, is a traditional Chinese medicine commonly used for the treatment of rheumatoid arthritis. However, the mechanisms underlying the effects of Eucommia in the treatment of arthritis of the knee require further study. The present study investigated the effects of an aqueous extract of Eucommia on the articular cartilage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
0
19
0
2
Order By: Relevance
“…Recent evidence has shown that Aucubin possesses anti-inflammatory property and inhibits NF-κB activation [22]. Moreover, an interesting study addressing the pharmaceutical effects of Eucommia ulmoides, a native Chinese medicinal herb whose major ingredient is Aucubin, indicates that it can inhibit inflammatory factors and prevents the degradation of the cartilage matrix in rats with OA [25]. Consistent with these reports, the present study confirms the anti-inflammatory and chondro-protective role, as well as the biosafety, of Aucubin at the cellular level.…”
Section: Discussionmentioning
confidence: 98%
“…Recent evidence has shown that Aucubin possesses anti-inflammatory property and inhibits NF-κB activation [22]. Moreover, an interesting study addressing the pharmaceutical effects of Eucommia ulmoides, a native Chinese medicinal herb whose major ingredient is Aucubin, indicates that it can inhibit inflammatory factors and prevents the degradation of the cartilage matrix in rats with OA [25]. Consistent with these reports, the present study confirms the anti-inflammatory and chondro-protective role, as well as the biosafety, of Aucubin at the cellular level.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in this study, we observed that HCHF synovial fluid, had remarkable effects on both synovial macrophages and chondrocytes, however, an overall profile of cytokines, chemokines and other signalling proteins of the synovial fluid from the two group of animals is required to clearly elucidate the association between the diet-induced obesity and OA. Additionally, we obtained joint synovial fluid sample by a standard lavage procedure [ 78 ]. Nonetheless, it is possible that different concentrations of synovial fluid analytes can be generated by the collection process alone, in addition to any changes due to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that a lower Mankin's grade induced by Eucommia is involved in histopathological examination. The levels of MMP-1, MMP-3, and MMP-13 in the serum and synovial fluid are negatively controlled by Eucommia [ 77 ]. These might be associated with downregulation of PI3K/Akt signaling pathway [ 78 ].…”
Section: Anticatabolic Activity Of Tcmmentioning
confidence: 99%